2021
DOI: 10.1177/09540083211009284
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxymethylene/thermoplastic polyamide elastomer blends: Morphology, crystallization, mechanical, and antistatic properties

Abstract: Polyoxymethylene/thermoplastic polyamide elastomer (POM/TPAE) blends were prepared through melt extrusion in an attempt to improve the toughness and electrical properties of POM. The TPAE used in the study had the permanent antistatic effect, and its brand was MV2080. Acrylonitrile-butadiene-styrene copolymer grafted maleic anhydride (ABS-g-MAH) was added while preparing the POM/TPAE blends to improve the compatibility between TPAE and POM. The effects of TPAE and ABS-g-MAH on the morphologies, melting crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Therefore, how to balance the mechanical properties and antistatic properties of the material would be the focus of future research. Fang et al 63 developed an antistatic thermoplastic polyamide elastomer (TPAE)/POM composite and researched the effect of acrylonitrile‐butadiene‐styrene copolymer grafted maleic anhydride (ABS‐MAH) as a compatibilizer on the antistatic properties of TPAE/POM. This result indicated that the conductive network formed by TPAE in the composites was more uniformly distributed after the addition of the ABS‐MAH, thus reducing the surface resistivity of the composites.…”
Section: Influence Factors Of Antistatic Performancementioning
confidence: 99%
“…Therefore, how to balance the mechanical properties and antistatic properties of the material would be the focus of future research. Fang et al 63 developed an antistatic thermoplastic polyamide elastomer (TPAE)/POM composite and researched the effect of acrylonitrile‐butadiene‐styrene copolymer grafted maleic anhydride (ABS‐MAH) as a compatibilizer on the antistatic properties of TPAE/POM. This result indicated that the conductive network formed by TPAE in the composites was more uniformly distributed after the addition of the ABS‐MAH, thus reducing the surface resistivity of the composites.…”
Section: Influence Factors Of Antistatic Performancementioning
confidence: 99%
“…However, poor impact strength, high UV sensitivity, and low thermal resistances may restrict its further application. [1][2][3][4] To tailor the functionality of POM and extend its applications, several studies were conducted to achieve a higher toughness for POM composites reinforced by elastomers [5,6] and mineral fillers. [7,8] The toughening of POM by incorporating elastomers was reported in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…PAEs have been used in thermoplastic blends as toughening agent or impact modifiers because they possess high impact resistance even at low temperatures 18–20 . Another important application of PAEs is as non‐migratory internal antistatic agent for many polymers such as polyethylene, polystyrene, polyoxymethylene 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…3,[12][13][14][15][16][17] PAEs have been used in thermoplastic blends as toughening agent or impact modifiers because they possess high impact resistance even at low temperatures. [18][19][20] Another important application of PAEs is as nonmigratory internal antistatic agent for many polymers such as polyethylene, polystyrene, polyoxymethylene. 20,21 Chemical structure, morphology, and composition of copolymers are directly related to their macro-scale properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation